Watershed Approach in Rainfed Afforestation - Jha, Mohan (Indian Forester, 1998)
In India most of the Afforestation Programmes are rainfed. In order to make the successful afforestation in degraded forest it is important to treat the area on the basis of watershed unit. Instead of carrying out afforestation of isolated patches. it is suggested to treat whole watershed depending of the type of area. soil status. slope and water retention capacity. During the rainy season. the vegetation suffers from water deficit situation at upper part. and due to prolonged wet condition on lower parts of the toposequense at a time. In a case study of Amravati. total 700 ha area was treated after dividing it into small micro-watershed and has shown excellent result. In-situ conservation of moisture in watershed leads to luxurious growth of vegetation and successful afforestation. Suitable conservation and storage structures at appropriate locations in micro-watershed lead to recharge of ground water. Increase in ground water table is being reflected in 11 dug wells in the watershed.